2010
DOI: 10.1007/s10695-010-9400-0
|View full text |Cite
|
Sign up to set email alerts
|

A reference growth curve for nutritional experiments in zebrafish (Danio rerio) and changes in whole body proteome during development

Abstract: Zebrafish is one of the most used vertebrate model organisms in molecular and developmental biology, recently gaining popularity also in medical research. However, very little work has been done to assess zebrafish as a model species in nutritional studies in aquaculture in order to utilize the methodological toolbox that this species represents. As a starting point to acquire some baseline data for further nutritional studies, growth of a population of zebrafish was followed for 15 weeks. Furthermore, whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 67 publications
5
50
2
1
Order By: Relevance
“…Development from the juvenile to the sexual maturity stage marks the transition from a state of rapid body growth to a state of slow somatic growth (Gomez-Requeni et al 2010). Unexpectedly, the transcriptional levels of gh in the pituitary gland remained the highest among the pituitary transcripts without a significant change at 45 and 90 dpf (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Development from the juvenile to the sexual maturity stage marks the transition from a state of rapid body growth to a state of slow somatic growth (Gomez-Requeni et al 2010). Unexpectedly, the transcriptional levels of gh in the pituitary gland remained the highest among the pituitary transcripts without a significant change at 45 and 90 dpf (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Zebrafish grow rapidly from birth to w50 dpf when most individuals begin to allocate part of their dietary energy intake to sexual maturation, which coincides with a decrease in growth rates (Gomez-Requeni et al 2010). The pituitary gland is a key regulator of body homeostasis during development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Another recent work reports fish that appear to be significantly larger than those in the present study, with a final length of *33 mm and a body weight of 350 mg. 24 Whether strain differences partially account for these growth differences has not been evaluated. Given the larger starting and final lengths, 24 it would be of interest to determine if dietary composition differences produced similar growth responses in another zebrafish strain background or if earlier initiation of formulated feeds altered the growth parameters. Additionally, tank densities were different between the two studies, with the current study having three times the density of the previous work (e.g., current: *5.5 fish/L vs. *1.6 fish/L).…”
Section: Smith Et Almentioning
confidence: 99%
“…requirements may be predicted based on other nutrition studies using teleost models, [20][21][22][23] few nutrient requirement studies have been formally presented in the research literature for zebrafish. 3,24,25 Nevertheless, although zebrafish nutrition and obesity research is still developing compared with rodent models, 26 the information reported from decades of rodent nutrition research may be used to rapidly test dietary compositions for a variety of growth and eventual health-related outcomes.…”
Section: Introductionmentioning
confidence: 99%